(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Internet of Thing (IoT) connects physical artifacts to form a network. Maximizing network existence and maximizing use of the network is a key priority. Study is performed on parameters such as network existence with an Internet of Thing (IoT) viewpoint and routing protocol efficiency measurements utilizing parameters such as network resilience, network life, reliability, throughput, etc. We are focusing on an algorithm to improve IoT Low Energy Adaptive Clustering Hierarchy (LEACH) routing. The primary objective of our paper is to carry out simulation studies on routing protocols, in particular Low Energy Adaptive Clustering Hierarchy (LEACH)[6], Cycle-Based Data Aggregation Scheme (CBDAS)[6], Grid Based Hybrid Network Deployment (GHND), Improved Grid Based Hybrid Network Deployment (IGHND) for an Internet of Thing (IoT) and to use the MATLAB simulator for Low Energy Adaptive Clustering Hierarchy (LEACH) for Internet of Thing (IoT) output evolution.